1997
DOI: 10.1021/bi9622884
|View full text |Cite
|
Sign up to set email alerts
|

Active Site Mutants Implicate Key Residues for Control of Color and Light Cycle Kinetics of Photoactive Yellow Protein

Abstract: To understand how the protein and chromophore components of a light-sensing protein interact to create a light cycle, we performed time-resolved spectroscopy on site-directed mutants of photoactive yellow protein (PYP). Recently determined crystallographic structures of PYP in the ground and colorless I2 states allowed us to design mutants and to study their photosensing properties at the atomic level. We developed a system for rapid mutagenesis and heterologous bacterial expression for PYP apoprotein and gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

36
261
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(301 citation statements)
references
References 20 publications
36
261
4
Order By: Relevance
“…Structural changes in the ␤4-␤5 and ␣3-␣4 loops would be expected to affect photocycle dynamics because of the presence of critical residues in those regions (26,27). As in E-PYP, the ␤4-␤5 loop is flexible in Ppr-PYP, evidenced by high B factors in this region in chains A and B and its disorder in chain C. The disorder of the ␤4-␤5 loop of chain C is caused by a weak packing interaction between it and the N-terminal helices of chain A, which are similarly disordered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural changes in the ␤4-␤5 and ␣3-␣4 loops would be expected to affect photocycle dynamics because of the presence of critical residues in those regions (26,27). As in E-PYP, the ␤4-␤5 loop is flexible in Ppr-PYP, evidenced by high B factors in this region in chains A and B and its disorder in chain C. The disorder of the ␤4-␤5 loop of chain C is caused by a weak packing interaction between it and the N-terminal helices of chain A, which are similarly disordered.…”
Section: Resultsmentioning
confidence: 99%
“…A R. centenum Ppr knockout showed no defects in phototaxis but had lower levels of expression of chalcone synthase, an enzyme involved in photoprotection through flavonoid biosynthesis (25). Although the PYP domain of Ppr (Ppr-PYP) is 45% identical in sequence to E-PYP and has similar or identical residues to all those suggested to be critical to absorption spectra and photocycle dynamics in E-PYP (26,27), Ppr-PYP has a considerably slower photocycle than E-PYP (25). Furthermore, as Ppr-PYP controls the activity of a histidine kinase, its study affords not only the opportunity to understand the signaling mechanism of PYPs, but of the entire class of PAS-domain-regulated sensor histidine kinases, which are ubiquitous in bacteria (28).…”
mentioning
confidence: 99%
“…The agreement between theoretical results and experimental data for PYP G seems to point out that the interaction between protein and chromophore, which has been neglected here, is similar in both ground and excited states. Indeed, the effect of mutants on excitation energies has been at most recorded to be 0.1 eV, for instance, when Glu-46 is replaced by Gln (34). On the other hand, in a recent theoretical study of the phenolate anion in the environment of PYP, He et al (42) have shown that the The results are compared to available experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, that the amino acid residue Glu-46 acts as the actual proton donor to the chromophore has been seen with IR techniques (32,33). The cycle is completed when the PYP G structure is recovered by means of a protein-mediated thermal process (34).…”
Section: Model Compound and Geometriesmentioning
confidence: 99%
“…Recent progress in experimental techniques made it possible to prepare PYP with an isotope-labeled chromophore (9) and a site-directed mutant of PYP (19,27). These techniques have enabled assignment of the vibrational modes.…”
mentioning
confidence: 99%